Isolation of streptococcus tigurinus - a novel member of streptococcus mitis group from a case of periodontitis - Dhotre, Shree V.; Mehetre, Gajanan T.; Dharne, Mahesh S.; Suryawanshi, Namdev M.; Nagoba, Basavraj S. (FEMS Microbiology Letters, 2014)
Streptococcus tigurinus is a new member of the Streptococcus viridians group and is closely related to Streptococcus mitis, Streptococcus pneumoniae, Streptococcus pseudopneumoniae, Streptococcus oralis, and Streptococcus infantis. The type strain AZ_3a(T) of S. tigurinus was originally isolated from a patient with infective endocarditis. Accurate identification of S. tigurinus is facilitated only by newer molecular methods like 16S rRNA gene analysis. During the course of study on bacteraemia and infective endocarditis with reference to periodontitis and viridians group of streptococci, a strain of S. tigurinus isolated from subgingival plaque of a patient with periodontitis identified by 16S rRNA gene analysis, which was originally identified as Streptococcus pluranimalium by Vitek 2. Confirmation by 16S rRNA gene analysis showed 99.39% similarity (1476/1485 bp) with S. tigurinus AZ_3a(T) (AORU01000002). To the best of our knowledge, this is the first report of isolation of S. tigurinus from the oral cavity of a periodontitis patient.
Keywords: periodontitis; Streptococcus tigurinus; VGS